The starlikeness and convexity of multivalent functions involving certain inequalities - Irmak, HÄuseyin; Raina, R. K. (Revista Matemática Complutense, 2003)
In the present paper, a theorem for the starlikeness and convexity of multivalent functions involving certain inequalities is given. Some interesting consequences of the main result are also mentioned.